Surgical Management of Thumb Carpometacarpal Osteoarthritis: A Systematic Review, Network Meta-analysis, and Longitudinal Analysis of Surgical Complications - Annora Ai-Wei Kumar, BBioMedSc; Matthew Lawson-Smith, MBBCh BAO (Journal of Hand Surgery Global Online)
Purpose: Thumb carpometacarpal osteoarthritis (CMC OA) is a common condition associated with functional limitations and pain. Surgical interventions for CMC OA include simple trapeziectomy, ligament reconstruction and tendon interposition, arthrodesis, and joint replacement. The aim of this review was to evaluate the comparative effectiveness of surgical techniques. Methods: A systematic review was performed, and the Medline, EMBASE, and SCOPUS databases were searched. Randomized controlled trials (RCTs) investigating the surgical management of CMC OA were included. The outcomes of interest were long-term pain reduction (visual analog scale), complications, and functional improvement (Disabilities of Arm, Shoulder and Hand questionnaire). Bayesian network meta-analyses were conducted, and longitudinal analysis of complication severity was performed using the Kruskal-Wallis H test. Results: There were 26 RCTs included, representing 19 surgical techniques and 1,193 hands. The average follow-up period was 29 months. In the analyses of pain, simple trapeziectomy ranked first, and trapeziectomy with button ranked last. Uncemented joint replacement ranked first in the analyses of function. Trapeziectomy alone demonstrated the most favorable results regarding avoidance of complications, and arthrodesis with plate and screw ranked last in the analysis of complications. Alternative surgical techniques were associated with a relative increase in complication severity across all time periods (χ2(2) = 22.92, 46.82, and 7.01 after 0–3, 3–12, and 12+ months; P < .001, <.001, and .03, respectively). Conclusions: Our findings demonstrate that simple trapeziectomy is effective at relieving the pain associated with CMC OA and minimizing postoperative complications, demonstrating a relative increase in both the number and severity of complications after alternative surgical techniques. Clinical relevance: Our review supports the use of simple trapeziectomy as the mainstay of surgical management of CMC OA, providing the foundation for research investigating metacarpal subsidence, trapeziometacarpal biomechanics, and implant dynamics in patients with CMC OA.